2017
DOI: 10.1177/0363546517720198
|View full text |Cite
|
Sign up to set email alerts
|

Does Additional Biceps Augmentation Improve Rotator Cuff Healing and Clinical Outcomes in Anterior L-Shaped Rotator Cuff Tears? Clinical Comparisons With Arthroscopic Partial Repair

Abstract: There was no significant difference in the clinical outcomes and retear rate of anterior L-shaped tears between biceps augmentation and partial tendon repair. Additional biceps augmentation proved to have no enhancement in tendon healing. A precise method such as only partial tendon repair for reducing the footprint exposure without undue tension may be considered as one of the treatment options for large anterior L-shaped rotator cuff tears.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 21 publications
(32 reference statements)
1
27
0
Order By: Relevance
“…In conflict with these findings, a multipatch comparative study 29 found no difference in failure rate between xenograft (Restore) and two different patches; human allograft (Graftjacket) or synthetic (Artelon). Among the observational comparative studies, significantly lower rates of re-tears were reported with augmentation using synthetic (Repol Angimesh), 30 autograft (fascia lata) 13 or allograft patches (Arthroflex and Allocover), 40 45 while no improvement in re-tears was observed following augmentation with DX (reinforcement matrix), 41 long head of biceps tendon autograft 43 or for the Restore 34 patch.…”
Section: Resultsmentioning
confidence: 99%
“…In conflict with these findings, a multipatch comparative study 29 found no difference in failure rate between xenograft (Restore) and two different patches; human allograft (Graftjacket) or synthetic (Artelon). Among the observational comparative studies, significantly lower rates of re-tears were reported with augmentation using synthetic (Repol Angimesh), 30 autograft (fascia lata) 13 or allograft patches (Arthroflex and Allocover), 40 45 while no improvement in re-tears was observed following augmentation with DX (reinforcement matrix), 41 long head of biceps tendon autograft 43 or for the Restore 34 patch.…”
Section: Resultsmentioning
confidence: 99%
“…Biceps augmentation in a different direction or partial repair has been introduced as a surgical repair technique for anterior L-shaped rotator cuff tear. Jeon et al 4 compared biceps augmentation that was performed to cover the cuff footprint in the anterior-to-posterior direction by cutting the tendon insertion and partial repair for an anterior L-shaped rotator cuff tear. Despite improved postoperative shoulder function, the retear rate of the 2 techniques was not significantly different (32% in biceps augmentation vs 39% in partial repair).…”
Section: Discussionmentioning
confidence: 99%
“…The rotator cuff tear pattern is recognized by preoperative magnetic resonance imaging and confirmed during arthroscopic surgery. An anterior L-shaped rotator cuff tear is defined as a tear that is longer in the medial-to-lateral direction than in the anterior-toposterior direction, with exposure of the biceps tendon 4 (Fig 1A, B).…”
Section: Surgical Technique Preoperative Evaluationmentioning
confidence: 99%
“…Interestingly, radiological findings seemed to closely echo patient-reported outcome measures (PROMs). Three studies 35,65,67 found no significant improvement in either PROMs or rate of re-tear, whereas a further five studies 26,33,40,42,68 reported significant improvements in both functional outcome scores and radiologically defined repair failure. This lends support to the notion that repair success is intimately linked with symptom resolution.…”
Section: Total (95% Ci)mentioning
confidence: 94%
“…30 Among the observational comparative studies, significantly lower rates of re-tears were reported after augmentation with synthetic (Repol Angimesh), autograft (fascia lata) or allograft patches (Arthroflex and Allocover), whereas no improvement in re-tears was observed following augmentation with a long head of biceps tendon autograft or for the Restore patch. 33,[39][40][41][42][43]67,71 Non-comparative studies Re-tear rate was assessed by 31 non-comparative studies, with a wide range of re-tear rates reported for each graft type [human allograft (0-25%, n = 7), human autograft (7-100%, n = 4), xenograft dermal (0-63%, n = 8), xenograft intestinal (8-90%, n = 4) and synthetic (7-62%, n = 8)].…”
Section: Re-tear (Including Radiological Assessments)mentioning
confidence: 99%